A chain mediation model for physical exercise and sleep quality - Yacheng Zhu; Qing Zhang; Ping Zhu; Yujie Dong; Liang Tan; Pingfan Liu; Zhenxiu Yi (Scientific Reports)
Abstract In recent years, there has been a significant increase in academic interest regarding the sleep quality of university students. Physical exercise has been extensively studied for its association with sleep quality in this population. However, the roles of anxiety and subjective well-being in mediating the relationship between physical exercise and sleep quality require further investigation. This study examines the interplay between physical exercise (independent variable), sleep quality (dependent variable), and the chain mediating effects of anxiety (mediator 1) and subjective well-being (mediator 2). A sample of 4,142 university students (1,525 males and 2,617 females; mean age = 19.05 ± 1.16 years) participated in this study. Cross-sectional self-report measures were used to assess physical exercise, anxiety levels, subjective well-being, and sleep quality. SPSS software facilitated descriptive statistics and correlation analyses. Subsequently, the SPSS PROCESS macro was employed to test and construct the chain mediation model described in the background and objective. The findings revealed a significant positive relationship between physical exercise and both sleep quality and subjective well-being, whereas a significant negative correlation was observed between physical exercise and anxiety. Furthermore, anxiety exhibited a negative association with sleep quality and subjective well-being. Importantly, anxiety and subjective well-being were found to sequentially mediate the link between physical exercise and sleep quality. By integrating clinical psychological (anxiety) and positive psychological (subjective well-being) factors, this study provides deeper insights into the mechanisms through which physical exercise influences sleep quality in college students. Encourage college students to engage in regular physical exercise, as this is often linked to anxiety, subjective well-being, and sleep quality, thereby leading to a higher quality of life.